Methodology for methane emission reduction by adjusted water management practice in rice cultivation - International Rice Research Institute (Gold Standard Foundation, 2023)
The methodology is applicable to measures that reduce anaerobic decomposition of organic matter in rice-cropping soils. Such measures include changing the water regime during the cultivation period from continuously to intermittently flooded conditions and/or a shortened period of flooded conditions, using the alternate wetting and drying method, adopting aerobic rice cultivation methods, and switching from transplanted to direct-seeded rice (DSR). This methodology can be applied to large and small-scale or micro-scale projects or PoAs.